PENGARUH INOVASI PRODUK TERHADAP VOLUME PENJUALAN BUSANA JAHIT UD. KITA JAYA DI TELUK DALAM - Zai, Alberta Yanti (PARETO : Jurnal Riset Bisnis dan Manajemen, 2024)
This research is motivated by logical arguments with the aim of this research being to find out how product innovation affects sales volume UD sewing clothing. We are victorious in Teluk Dalam. Primary data is used as a data source, namely data obtained directly from the research object through distributing questionnaires to customers of UD.Kita Jaya in Teluk Dalam, and the sample for this research is 36 respondents. The research method used is a quantitative method that is causal in nature and processed using simple linear regression analysis techniques. From the results of hypothesis testing, based on the partial test results of the product innovation variable (X) on sales volume, it is clear that UD's sewing fashion product innovation. Kita Jaya Di Teluk Dalam has a partial effect on the sales volume of UD sewing clothing. Kita Jaya Di Teluk Dalam, then based on simultaneous results it is known that product innovation has an effect on the sales volume of UD sewing clothing. We are victorious in Teluk Dalam. The suggestion of this research is that it is necessary to improve product quality so that product variants and designs can be very attractive to customers and of course pay attention to designs that are not too old-fashioned and pay attention to customer desires, then it is necessary to provide price discounts.